The Structure of Artefacts of Management Control in the Innovation Process: Does Exist Association with the Strategic Profile? - Fábio Frezatti; Diógenes de Souza Bido; Ana Paula Capuano da Cruz; Maria José de Camargo Machado (BBR: Brazilian Business Review)
This study investigates what is the role of strateg ic profiles and management control instruments in organisations’ innovation process. B ased in a survey using structural equation modelling (121 companies), we confirm that analyser , defender e prospector profiles are associated with strategic planning, balanced scorec ard (BSC) and rolling forecast. The reactor type is associated with lower use of artefacts. Our results confirm the linkage between incremental innovation and strategic planning and b etween radical innovation and BSC. These findings reflect the alignment between strate gic types, the availability of instruments and intensity of innovation, which is useful inform ation with which to understand organisations and their market activities. This pap er bring information about specific management control instruments existence and the im pact for the intensity of the innovation that is relevant for management and must stimulate organizations to be consistent in the cases that the strategic profile is a clear long term def inition or see the possibility of change when it is not the desired one.